2017
DOI: 10.18632/oncotarget.15554
|View full text |Cite
|
Sign up to set email alerts
|

Palliative radiotherapy for gastric cancer: a systematic review and meta-analysis

Abstract: Background/PurposeTo review the efficacy and toxicity of palliative radiotherapy (RT) for symptomatic locally advanced gastric cancer (GC) and to determine the optimal RT schedule for symptom palliation.MethodsWe searched MEDLINE and CENTRAL for eligible studies published from 1995 to 2015. Outcomes of interest were relief of bleeding, pain and obstruction.RESULTSSeven non-comparative observational studies were included. There were large variations in RT dose and fractionation. The pooled overall response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 17 publications
3
50
0
10
Order By: Relevance
“…Our results are consistent with outcomes of palliative radiotherapy for other tumour sites (2,3,5). In a systematic review of palliative RT for hemoptysis in lung cancer, Fairchild et al have reported that there was no significant difference in response rates between high dose versus low dose regimens (2).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are consistent with outcomes of palliative radiotherapy for other tumour sites (2,3,5). In a systematic review of palliative RT for hemoptysis in lung cancer, Fairchild et al have reported that there was no significant difference in response rates between high dose versus low dose regimens (2).…”
Section: Discussionsupporting
confidence: 88%
“…Effective treatments with low toxicity are preferred for patients with advanced disease and limited life expectancy. Palliative RT has been shown to be effective in treating bleeding at other cancer sites, including lung and gastric cancers (2)(3)(4)(5). It has the benefit of controlling the symptoms while reducing the burden of symptoms.…”
mentioning
confidence: 99%
“…However, there is limited research on palliation of symptoms resulting from primary gastric tumor. A systematic review and meta‐analysis of published studies on the efficacy of palliative gastric RT found that there were no prospective studies examining this issue . The interpretation of the retrospective studies on the efficacy of palliative gastric RT is limited by the use of concurrent chemotherapy, different definitions of endpoints and the use of different radiation dose fractionation schedules.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines mention that hypo-fractionated radiotherapy is an effective and well-tolerated treatment option for symptomatic locally advanced or recurrent disease [71] . In non-comparative observational studies, the overall response rates for bleeding, pain and obstruction symptoms were 74%, 67% and 68% respectively, low biological equivalent dose of > 39 Gy regimens appear to be adequate for symptom palliation [72] .…”
Section: Palliative Radiation Therapymentioning
confidence: 95%